Developmental change during a speciation event: evidence from planktic foraminifera. Issue 1 (February 2022) - Vanadzina, Karina; Schmidt, Daniela N.
Abstract: Studies in extant populations have shown that plasticity in developmental trajectories can contribute to the origin of novel traits and species divergence via the expression of previously cryptic variation in response to environmental change. Finding evidence for plasticity-led evolution in the fossil record remains challenging due to the poor preservation of developmental stages in many organisms. Planktic foraminifera are ideally suited for addressing this knowledge gap, because adult organisms in species in which development has been studied retain information about all the ontogenetic stages they have undergone. Here we map changes in the developmental trajectories of 68 specimens in the Globorotalia plesiotumida–tumida lineage of planktic foraminifera from the late Miocene until Recent using high-resolution computer tomography techniques. Our unique dataset shows that the transition from the ancestral G. plesiotumida to the descendant G. tumida is preceded by an increased variability in total cumulative volume—an important indicator of reproductive success in this taxon. We also find that the transition interval is marked by a distinct shift in developmental trajectory, which supports a rapid lineage division rather than gradual change. We suggest that high levels of plasticity—particularly in the early stages of development—have contributed to divergence in the ancestral morphology when subjected to a global cooling trend in the late Miocene. The large variation in developmental trajectories that we uncover within our samples emphasizes the need for high-throughput approaches in studies of ontogenetic change in the fossil record.